Integrative Management of School Principals in Instilling Moral Values Through the National Curriculum at Madrasah Ibtidaiyah Bina Akhlaq - Wahyu Sihab; Mohamad Joko Susilo (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to describe the principal's managerial strategy in integrating moral values into the national curriculum at MI Bina Akhlaq. The background of this research is the importance of character education in the world of basic education, especially madrasah, as a means of forming noble morals from an early age. The approach used is descriptive qualitative with data collection techniques through in-depth interviews, classroom observation, and documentation. The results showed that the principal used an integrative strategy through collaborative curriculum planning, strengthening the role of teachers as moral role models, and continuous internal supervision. This strategy allows for synergy between the academic content of the national curriculum and Islamic moral values. This study recommends the need for ongoing training for teachers and principals in moral values-based curriculum management.